Sosialisasi dan Edukasi Alokasi Dana Desa kepada Aparatur Desa di Kabupaten Timor Tengah Selatan - Jefirstson Richset Riwukore (Jurnal Pemberdayaan Ekonomi, 2023)
Purpose: The purpose of implementing community service activities is to provide education to village officials so that they have an understanding of the complexity of village fund allocations and the ability to evaluate and analyze problems in village fund allocation management. Methodology: The implementation of this community service uses the focus group discussion (FGD) method. The partners involved were all village heads in the District of Timor Tengah Selatan, and the Dinas Pemberdayaan Masyarakat of Timor Tengah Selatan District. Participants were determined by non-probability by purposive sampling. Based on this technique, the number of FGD participants was 267 people. The mechanism for implementing FGDs consists of discourse and evaluations. Discourse are conducted through information sharing, knowledge sharing, and relations. Meanwhile, the evaluation of the results was carried out through a non-test method using a direct-open questionnaire. Results: The implementation of village fund allocation management in the village is still a problem and obstacle caused by the limited human resources of the village head, limited supporting infrastructure, limited guidance and assistance, capacity building activities for village officials who are not yet oriented to village needs, programming and policies that are not adaptive between interests. government to the village, and sectoral ego. Conclusion: The activities carried out can educate so that participants have knowledge of the management of village fund allocations. In addition, participants were able to evaluate problems and obstacles in implementing village funds, especially those related to the allocation of village funds. In addition, participants were able to reconstruct recommendations for improving the management of village fund allocations to village fund stakeholders, especially the government, from the village head itself to the central government level.